The reasons interfering visit of paid sports and improving lessons by potential clients - P. V. Pasechnik (Путеводитель предпринимателя)
The article actualizes the problem of identifying the risks associated with the prediction of the possible reasons that prevent a visit paid health and fitness classes of economically active population. Presents the results of the survey of potential customers between the ages of 30 and 59 years who, in the opinion of the author may serve as a basis for making timely and correct measures for risk prevention.